Manajemen Risiko dalam Program Bantuan Sosial di Labuhanbatu Utara: Perspektif Ekonomi Islam dan Maqasid al-Syariah - Ritonga, Dendi Dwi; Yanti, Nursantri; Harahap, M. Ikhsan (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2025)
This study investigates risk management in social assistance programs in North Labuhanbatu Regency (PKH, BPNT, YAPI, and PBI BPJS Kesehatan), with emphasis on Islamic economic perspectives. Using a qualitative case study through interviews, observations, and document analysis, it reveals that despite formal reference to Government Regulation No. 04/2019 and ISO 31000:2018, implementation faces major challenges: mistargeting, data duplication, distribution delays, limited human resources, weak coordination, and inadequate technology. These hinder program effectiveness. From an Islamic economics lens, such flaws violate principles of justice, trustworthiness, and protection of wealth. Mistargeting denies the rights of the poor, while weak oversight risks fund misuse. Applying maqasid al-shariah demands strengthening data systems, improving human resources as a form of trustworthiness, and ensuring transparent distribution for maslahah. The study concludes that effectiveness and barakah (blessing) require integrating modern risk management with Islamic ethics, offering a governance model that is efficient, accountable, just, and sustainable.